Dysregulated Circulating Apoptosis- and Autophagy-Related lncRNAs as Diagnostic Markers in Coronary Artery Disease. (1st September 2021) - Zhang, Lijiao; Lou, Dayuan; He, Dan; Wang, Ying; Wu, Yuhang; Cao, Xinyang; Qu, Peng
Abstract : Objective . Increasing evidence emphasizes the implications of dysregulated apoptosis and autophagy cellular processes in coronary artery disease (CAD). Herein, we aimed to explore apoptosis- and autophagy-related long noncoding RNAs (lncRNAs) in peripheral blood of CAD patients. Methods . The mRNA and lncRNA expression profiles were retrieved from the Gene Expression Omnibus (GEO) database. With ∣ fold   change ∣ > 1.5 and adjusted p value < 0.05, differentially expressed apoptosis- and autophagy-related mRNAs were screened between CAD and healthy blood samples. Also, differentially expressed lncRNAs were identified for CAD. Using the psych package, apoptosis- and autophagy-related lncRNAs were defined with Spearson's correlation analysis. Receiver operating characteristic (ROC) curves were conducted for the assessment of the diagnosed efficacy of these apoptosis- and autophagy-related lncRNAs. Results . Our results showed that 24 apoptosis- and autophagy-related mRNAs were abnormally expressed in CAD than normal controls. 12 circulating upregulated and 1 downregulated apoptosis- and autophagy-related lncRNAs were identified for CAD. The ROCs confirmed that AC004485.3 (AUC = 0.899 ), AC004920.3 (AUC = 0.93 ), AJ006998.2 (AUC = 0.776 ), H19 (AUC = 0.943 ), RP5-902P8.10 (AUC = 0.956 ), RP5-1114G22.2 (AUC = 0.883 ), RP11-247A12.1 (AUC = 0.885 ), RP11-288L9.4 (AUC = 0.928 ), RP11-344B5.2 (AUC = 0.858 ), RP11-452C8.1 (AUC = 0.929 ), RP11-565A3.1 (AUC = 0.893 ), and XXbac-B33L19.4 (AUC = 0.932 ) exhibited good performance in differentiating CAD from healthy controls. Conclusion . Collectively, our findings proposed that circulating apoptosis- and autophagy-related lncRNAs could become underlying diagnostic markers for CAD in clinical practice.